Perancangan Human Resource Management System pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Lingga Berbasis Web - Rizky Rianda; Febri Hadi; Rima Liana Gema (Jurnal KomtekInfo, 2021)
Human Resource Management System (HRMS) is a system that can simplify the process of handling various human resource management activities in a company in a structured and comprehensive manner. HRMS can assist management in carrying out their duties and assist companies in achieving goals and minimizing the risk of loss due to errors in managing employee data, especially in terms of payroll. The number of components in managing employees in a company will make the management in carrying out their duties a little more complicated and complex. So it is necessary to have a system that can manage all components of employee management in one centralized system. In this study, a web-based HRMS has been designed that can be used by employee management and also the employees themselves. From the results of the study, it is known that the implementation of HRMS at the Regional Drinking Water Company (PDAM) of Lingga Regency can assist employee management in managing all employee data including data collection, planning, management, and directing activities effectively and efficiently and can minimize the human error factor.